Devising the policy of funds allocation in the decision-making process under the budget and tax management - Kuzmynchuk, Nataliia; Mardus, Nataliia; Davydov, Oleksandr; Yevtushenko, Viktoriia; Melen, Olena; Kharchenko, Alla (ПП "Технологічний Центр", 2022)
This paper reports a seminal study whose relevance and significance are related to strengthening the importance of improving the distribution policy by introducing a model for optimizing the allocation of budget funds in the decision-making process. It has been determined that the potential of life support of the population in a region (PLSP in a region) acts as a tool for examining the resources in the region in terms of their capability to meet the needs of the population of the region in the current period and in the future. Based on the anthropocentric approach, it was determined that the main strategic resource is human potential that possesses a set of characteristics (components), which reflect its physical potential, the potential abilities and knowledge, as well as property potential. The implementation of the PLSP concept in the region has caused an urgent desire to study modern problems related to the budget and tax management of regional development, specifically, the management of budget expenditures at the stage of their allocation using modern means for supporting these processes. The expediency of using models of mathematical programming to determine the effective structure of the budget, taking into consideration the rate of inflation and the use of the methodology for calculating real wages, has been established. The following values for most priority areas of budget financing were calculated: the level of development of social infrastructure (11 %), the level of vocational training (29 %), the level of remuneration and entrepreneurial income (21 %), and the level of social payments to the population (14 %). It has been found that when a new allocation of budget funds is implemented, the value of the achieved level of PLSP development in a region could increase by 9 % compared to 2021. The proposed approach is a permanently important prerequisite for the formation of priority areas of budget financing for the components of PLSP in a region in the process of producing and implementing universal and specific solutions in the field of budget and tax management.

Проведено дослідження, актуалізація та цінність якого спрямована на посилення значущості питання удосконалення політики розподілу шляхом впровадження моделі оптимізації розподілення бюджетних коштів у процес прийняття рішень. Визначено, що потенціал життєзабезпечення населення в регіоні (ПЖН в регіоні) виступає інструментом дослідження ресурсів регіону з точки зору їх можливості забезпечувати потреби населення регіону в поточному періоді та в перспективі. Ґрунтуючись на антропоцентричному підході встановлено, що основним стратегічним ресурсом є людський потенціал, що має сукупність характеристик (компонент), які відображають його фізичний потенціал, потенціал здібностей і знань, майновий потенціал. Реалізація концепції ПЖН в регіоні викликала нагальну потребу дослідження сучасних проблем бюджетно-податкового управління розвитку регіонів, зокрема управління бюджетними видатками на стадії їх розподілу з використанням сучасних засобів забезпечення цих процесів. Визначено доцільність застосування моделей математичного програмування для визначення ефективної структури бюджету з урахуванням темпів інфляції та використання методики розрахунку реальної заробітної плати. Отримано значення найбільш пріоритетних напрямів бюджетного фінансування: рівень розвитку соціальної інфраструктури (11 %), рівень професійної підготовки (29 %), рівень оплати праці та підприємницького доходу (21 %) та рівень соціальних виплати населенню (14 %). Встановлено, що за умови нового розподілу бюджетних коштів величина досягнутого рівня розвитку ПЖН в регіоні збільшиться на 9 % порівняно з 2021 р. Запропонований підхід виступає перманентно важливою передумовою формування пріоритетних напрямів бюджетного фінансування за компонентами ПЖН в регіоні у процесі продукування і реалізації універсальних й специфічних рішень в сфері бюджетно-податкового управління.
Формування політики розподілу коштів у процесі прийняття рішень при бюджетно-податковому управлінні
Keywords: allocation policy; optimal distribution; potential of life support of the population in a region; budget and tax management; політика розподілу; оптимальний розподіл; потенціал життєзабезпечення населення в регіоні; бюджетно-податкове управління